«Un esclavo que se llama Antonio»: venta de dos esclavos asiáticos en Galicia a inicios del siglo XVII - Ménard, Caroline (Cuadernos de Estudios Gallegos, 2012)
Slavery has existed in the Iberian Peninsula since the Antiquity and up to the Modern Era - and moreover, it was not restricted to the submission of people coming from Africa. This paper will look at the sale of two slaves originally from Asia, Antonio and Domingo, in 1603 in the port of Vigo - it will explore their journey, the role of the Carreira da India Portuguese mariners as sailors, their origin and sale price. Antonio and Domingo might represent a minority compared to all the slaves living at that time in Galicia, but their difference is a rich illustration of the process as it was then working.
Keywords: século XVII

La pesca gallega en Terranova, siglos XVI-XVIII - Ménard, Caroline (Universidade de Santiago de Compostela. Servizo de Publicacións e Intercambio Científico, 2007)

Un mémoire écrit par Bacqueville de la Potherie? - Ménard, Caroline (Newfoundland Studies, 2006)
An article from Newfoundland Studies, on Érudit.